2013
DOI: 10.1111/jocn.12169
|View full text |Cite
|
Sign up to set email alerts
|

Searching for reintegration: life experiences of people with schizophrenia

Abstract: This research focused on reintegrating process of people with schizophrenia and developing culturally sensitive nursing care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
7
0
Order By: Relevance
“…With regard to the meaning of mental illness, a painful, suffering and multifaceted experience was described herein by the participants, congruent to previous studies [ 54 , 103 107 ]. Participants clearly described two distinguished sources of suffering; firstly the distressing experiences stemming from the pathophysiology of the disease and side effects of pharmacotherapy and secondly social stigma associated with mental illness and psychotropic medication.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…With regard to the meaning of mental illness, a painful, suffering and multifaceted experience was described herein by the participants, congruent to previous studies [ 54 , 103 107 ]. Participants clearly described two distinguished sources of suffering; firstly the distressing experiences stemming from the pathophysiology of the disease and side effects of pharmacotherapy and secondly social stigma associated with mental illness and psychotropic medication.…”
Section: Discussionsupporting
confidence: 87%
“…The significance of empathic and supportive relationships between consumers of mental health services and health professionals lies on evidence which shows that these qualities enhance understanding of healthcare professionals and reassurance towards people living with SMI. This in turn seems to make patients feel accepted, facilitating their social integration [ 54 , 124 , 139 143 ]. Overall, empathy, respect and availability provided by health professionals have been described in international literature as basic elements of the therapeutic relationship [ 47 , 67 , 104 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The care needs of elderly patients with schizophrenia are different from those of younger adult patients with the disease. Professionals need to know that the positive symptoms tend to be less severe in elderly patients than in younger adult patients, and that physical comorbidity is common in elderly patients (Ko, Smith, Liao, & Chiang, 2014). Moreover, older age is a risk factor for the side effects of antipsychotics (Jeste & Maglione, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies (Avieli et al, 2016;Moonen et al, 2016) pointed out that interpretations of a person's suffering could likely provide deeper insights into the meaning of the lived experience. Supporting this assumption, Ko et al (2014) found that reflections on the suffering and of the spiritual beliefs in the patient's own cultural context could work as a means of finding ways of reintegration through regaining control and finding inner peace. In a meta-ethnography of 17 qualitative studies, Kaite et al (2015) presented the profound loss of identity, pain of having had one's life stolen, and an ongoing struggle for reconciliation with the self and the illness as core themes of living with severe mental illness.…”
Section: Accumulated Suffering In Living With Schizophreniamentioning
confidence: 90%